Oxysulfide solid-state electrolyte and method for preparing the same

CN122889824APending Publication Date: 2026-10-09GUANGZHOU VOCATIONAL COLLEGE OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610709479.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-21
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本申请提供一种氧硫化物固态电解质及其制备方法,以解决现有技术中空气稳定性差、易水解产生有毒硫化氢气体、性能一致性差,粒径差异性大且电化学窗口较窄等问题

Benefits of technology

[0020](1)本申请实施例采用xLi2O・yLiWS2・Iz三元组分设计,通过Li2O引入电负性更强的氧原子部分取代硫化物骨架中的硫原子,形成键能显著更高的Li-O键与W-O键;氧原子的引入降低了骨架中剩余硫原子的电子云密度与反应活性,从化学键本质上阻断了水分子与硫原子的亲核取代反应路径,既避免了有毒硫化氢气体的生成,又防止了水解反应导致的晶体骨架断裂与锂离子传输通道坍塌,使电解质在相对湿度50%、25℃空气中暴露24h后电导率保留率仍达87.6%-94.2%,硫化氢释放量低于0.1ppm,三者协同作用实现离子电导率的显著提升,25℃下离子电导率可达1-7mS/cm,远优于传统二元氧硫化物电解质。同时,氧元素的引入增强了电解质的化学稳定性,抑制了硫化物的水解反应,大幅提升了空气稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889824A_ABST
    Figure CN122889824A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of solid electrolytes, in particular to an oxysulfide solid electrolyte and a preparation method thereof, the chemical composition of the oxysulfide solid electrolyte being xLi2O yLiWS2 zH2O z , wherein 0<=x<=3, 0<=y<=2, 0<=z<=1. Through the synergistic chemical bond regulation of ternary components and the anhydrous and oxygen-free low-temperature preparation process, the high air stability, the wide electrochemical window and the excellent batch consistency of the oxysulfide solid electrolyte are realized, and the application performance of the oxysulfide solid electrolyte in high-energy-density all-solid-state batteries is optimized. Therefore, the problems of poor air stability, easy hydrolysis to generate toxic hydrogen sulfide gas, poor performance consistency, large particle size difference and narrow electrochemical window in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid electrolyte technology, and in particular to an oxysulfide solid electrolyte and its preparation method. Background Technology

[0002] Solid-state electrolytes, as key materials in solid-state batteries, are crucial to their performance. Currently developed solid-state electrolytes include polymers, oxides, sulfides, and halides. By replacing existing liquid electrolytes with solid-state electrolytes possessing high ionic conductivity, all-solid-state batteries offer potential advantages in power characteristics, temperature adaptability, and other aspects, while ensuring high safety and high specific energy. This is expected to significantly enhance the competitiveness of electric vehicles in terms of driving range and charging capabilities.

[0003] In the research and development of solid-state electrolyte materials, sulfide systems are frequently chosen by Japanese and South Korean companies, with Toyota leading the way in the mass production of sulfide-based all-solid-state batteries. Currently, many domestic companies have entered the sulfide-based solid-state battery field, and there have been frequent positive developments, driving the development of sulfide-based solid-state batteries. In recent years, more and more companies have begun to invest in the research and development of sulfide-based all-solid-state batteries. However, no company has yet achieved large-scale production of sulfide-based all-solid-state batteries. Many challenges remain to be addressed, including poor air stability, easy hydrolysis producing toxic hydrogen sulfide gas, poor performance consistency, uneven particle size distribution, and a narrow electrochemical window.

[0004] Therefore, there is an urgent need in the field for a novel oxysulfide solid electrolyte that has high ionic conductivity, high air stability, and a simple preparation process, making it an ideal solid electrolyte material for use in solid-state batteries for new energy vehicles. Summary of the Invention

[0005] This application provides an oxysulfide solid electrolyte and its preparation method to solve the problems of poor air stability, easy hydrolysis to produce toxic hydrogen sulfide gas, poor performance consistency, large particle size difference and narrow electrochemical window in the prior art.

[0006] This application provides an oxygen sulfide solid electrolyte, characterized in that the chemical composition of the oxygen sulfide solid electrolyte is xLi₂O·yLiWS₂·I. z , where 0≤x≤3, 0≤y≤2, 0≤z≤1.

[0007] Optionally, the raw material source of the oxysulfide solid electrolyte is Li2O, LiWS2, and I.

[0008] Optionally, Li2O in the raw material can be replaced with Li2CO3 or LiOH.

[0009] Optionally, the ionic conductivity of the oxysulfide solid electrolyte at 25°C is 1-7 mS / cm.

[0010] This application also proposes a method for preparing an oxysulfide solid electrolyte, comprising the following steps:

[0011] S1: Mix raw materials Li2O, LiWS2 and elemental I and ball mill them, controlling the ball milling speed to 200-500 rpm and the ball milling time to 2-12 h, to obtain a mixed powder with a particle size of 100nm-100μm;

[0012] S2: The mixed powder obtained in S1 is placed in a protective gas atmosphere for heat treatment, and the protective gas flow rate is controlled at 50-150 sccm, the heat treatment temperature is 200-500℃, and the heat treatment time is 2-12h to obtain crude oxygen sulfide solid electrolyte.

[0013] S3: The crude oxygen sulfide solid electrolyte obtained in S2 is ground under a protective gas. The ground powder is then sieved through a 200-mesh sieve, and materials with a mesh size ≥ 200 are collected to obtain the oxygen sulfide solid electrolyte.

[0014] Preferably, the protective gas includes any one or a combination of at least two of argon, helium, and neon, with argon being the most preferred.

[0015] Preferably, the protective gas has a water content of <1 ppm and an oxygen content of <1 ppm.

[0016] Preferably, the ball milling is a high-energy mechanical ball milling process.

[0017] This application also proposes the use of an oxysulfide solid electrolyte for use in solid-state batteries for new energy vehicles.

[0018] This application also proposes a method for preparing an oxysulfide solid electrolyte and its application in an all-solid-state lithium-ion secondary battery.

[0019] Therefore, this application has at least the following beneficial effects:

[0020] (1) The embodiments of this application adopt a ternary component design of xLi2O・yLiWS2・Iz. By introducing oxygen atoms with stronger electronegativity into Li2O, the sulfur atoms in the sulfide skeleton are partially replaced, forming Li-O bonds and WO bonds with significantly higher bond energies. The introduction of oxygen atoms reduces the electron cloud density and reactivity of the remaining sulfur atoms in the skeleton, and fundamentally blocks the nucleophilic substitution reaction pathway between water molecules and sulfur atoms from the chemical bond. This avoids the generation of toxic hydrogen sulfide gas and prevents the crystal skeleton from breaking and the collapse of lithium ion transport channels caused by hydrolysis. After exposure to air at 50% relative humidity and 25°C for 24 hours, the conductivity retention rate of the electrolyte is still 87.6%-94.2%, and the hydrogen sulfide release is less than 0.1ppm. The three factors work synergistically to achieve a significant improvement in ionic conductivity. The ionic conductivity at 25°C can reach 1-7mS / cm, which is far superior to traditional binary oxygen sulfide electrolytes. At the same time, the introduction of oxygen enhances the chemical stability of the electrolyte, inhibits the hydrolysis reaction of sulfides, and greatly improves air stability.

[0021] (2) In the embodiments of this application, the raw material Li2O can be replaced with Li2CO3 or LiOH. These three raw materials are common industrial chemicals, widely available and inexpensive, which greatly reduces the preparation cost of solid electrolyte. Lithium carbonate and lithium hydroxide can undergo complete thermal decomposition reaction within the heat treatment temperature range of 200-500℃ set in this application. Lithium carbonate decomposes at 350-450℃ to generate highly active nano-sized lithium oxide and carbon dioxide, and lithium hydroxide decomposes at 250-400℃ to generate highly active nano-sized lithium oxide and water vapor. The nano-sized lithium oxide generated in situ has higher reactivity and can fully react with lithium sulfide and elemental iodine at a lower temperature to form a uniform oxysulfide crystal structure. The carbon dioxide and water vapor generated by decomposition can be carried out of the reaction system in time by a continuous flow of protective gas with a flow rate of 50-150 sccm. No solid impurities will remain in the electrolyte crystal, and no side reactions will occur with lithium sulfide, elemental iodine and other raw materials, thus ensuring the purity and performance stability of the electrolyte.

[0022] (3) In the embodiments of this application, the water content and oxygen content of the protective gas are controlled to be <1ppm and <1ppm, and the gas flow rate during the heat treatment process is 50-150sccm, which effectively isolates the moisture and oxygen in the air from the oxidation and corrosion of the raw materials and products, and ensures the purity of the electrolyte. The ball milling speed of 200-500rpm and the ball milling time of 2-12h can accurately control the particle size of the mixed powder in the range of 100nm-100μm. Finally, the product with uniform particle size is obtained by screening through a 200-mesh sieve, which ensures the consistency of the performance of different batches of products. At the same time, the refined grains increase the contact area between particles and reduce the reaction activation energy and particle size difference of subsequent heat treatment.

[0023] (4) In the embodiments of this application, the electronic structure of the electrolyte is optimized by co-doping of oxygen atoms and iodine atoms. The introduction of oxygen atoms increases the oxidation potential at the top of the valence band and inhibits the oxidative decomposition of the electrolyte under high voltage. The doping of iodine atoms reduces the reduction potential at the bottom of the conduction band and enhances the interfacial compatibility with the lithium metal anode. The synergistic effect of the two avoids the mutual restriction between ionic conductivity and stability caused by single element doping, and broadens the electrochemical window to 4.6-5.0V vsLi / Li⁺, stably matching high voltage cathode materials such as lithium nickel manganese oxide and lithium-rich manganese-based materials.

[0024] This solves the problems of poor air stability, easy hydrolysis to produce toxic hydrogen sulfide gas, poor performance consistency, large particle size difference and narrow electrochemical window in the existing technology.

[0025] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0026] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings, wherein:

[0027] Figure 1 This is a flowchart illustrating an oxysulfide solid electrolyte and its preparation method according to an embodiment of this application. Detailed Implementation

[0028] The technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0029] In the embodiments of this application, unless otherwise specified, the raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.

[0030] The present application will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present application in any way.

[0031] Example 1

[0032] This application provides an oxygen sulfide solid electrolyte, characterized in that the chemical composition of the oxygen sulfide solid electrolyte is xLi₂O·yLiWS₂·I. z , where 0≤x≤3, 0≤y≤2, 0≤z≤1.

[0033] The raw materials for the oxysulfide solid electrolyte are Li2O, LiWS2 and I.

[0034] In this context, Li2O in the raw material can be replaced with Li2CO3 or LiOH.

[0035] The ionic conductivity of the oxysulfide solid electrolyte at 25°C is 1 mS / cm.

[0036] This application also proposes a method for preparing an oxysulfide solid electrolyte, such as... Figure 1 As shown, it includes the following steps:

[0037] S1: Mix raw materials Li2O, LiWS2 and elemental I and ball mill them, controlling the ball milling speed at 200 rpm and the ball milling time at 2 h, to obtain a mixed powder with a particle size of 100 nm;

[0038] It is understood that in the embodiments of this application, the three raw materials, Li2O, LiWS2, and elemental I, are mechanically ball-milled at a controlled speed of 200 rpm for 2 hours to ensure a mixed powder with a uniform particle size distribution of 100 nm. This fully utilizes the mechanochemical effect to achieve molecular-level uniform mixing of the components at the nanoscale. For subsequent heat treatment, the activation energy of the reaction can be significantly reduced, allowing the crystal to complete ordered growth at low temperatures. The precisely controlled particle size range can avoid particle agglomeration and abnormal grain growth. This maximizes the reaction efficiency and product purity between raw materials and lays the microstructural foundation for the subsequent formation of continuous and uniform lithium-ion transport channels. It effectively avoids problems such as component segregation, excessive particle size differences, and incomplete reaction caused by traditional solid-phase mixing, ensuring the ionic conductivity and batch stability of the oxysulfide solid electrolyte.

[0039] S2: The mixed powder obtained in S1 is placed in a protective gas atmosphere for heat treatment. The protective gas flow rate is controlled at 50 sccm, the heat treatment temperature is 200℃, and the heat treatment time is 2h to obtain crude oxygen sulfide solid electrolyte.

[0040] It is understood that, in the embodiments of this application, by placing the product in a protective gas atmosphere with a water content of <1ppm and an oxygen content of <1ppm, and controlling the gas flow rate of 50sccm, the heat treatment temperature of 200℃, and the heat treatment time of 2, the crude oxygen sulfide solid electrolyte with a complete crystal structure and free from oxidation and hydrolysis impurities is ensured. Regarding the crystal growth process, this promotes short-range atomic diffusion to form a continuous three-dimensional lithium-ion transport framework, while eliminating internal stress and lattice defects introduced by high-energy ball milling. Regarding product purity and stability, the flowing protective gas can promptly remove volatile impurities such as CO2 and H2O generated by thermal decomposition, completely isolating the sulfide framework from external moisture and oxygen. This maximizes the retention of highly active ion transport channels synergistically constructed by the ternary components, while avoiding abnormal grain growth and sulfide decomposition caused by high temperatures. It effectively avoids problems such as decreased ionic conductivity, impurity residue, and batch performance fluctuations caused by traditional high-temperature sintering, ensuring the high ionic conductivity and chemical stability of the oxygen sulfide solid electrolyte.

[0041] S3: The crude oxygen sulfide solid electrolyte obtained in S2 is ground under a protective gas. The ground powder is then sieved through a 200-mesh sieve, and materials with a mesh size ≥ 200 are collected to obtain the oxygen sulfide solid electrolyte.

[0042] It is understood that in this embodiment, the crude oxygen sulfide solid electrolyte obtained in S2 is ground under a protective gas with a water content of <1ppm and an oxygen content of <1ppm. The ground powder is then sieved through a 200-mesh sieve, and materials with a mesh size of ≥200 mesh are collected. This process not only isolates the electrolyte from moisture and oxygen in the air by creating an inert atmosphere that is completely anhydrous and oxygen-free, thus preventing hydrolysis and oxidation reactions that could generate toxic hydrogen sulfide gas and impurities during grinding, but also ensures that the chemical purity and core ion transport performance of the electrolyte do not degrade. Furthermore, mechanical grinding effectively breaks up the soft agglomerates formed during heat treatment, making the particles monodisperse and preventing uneven coating and interface defects caused by large particle agglomeration, thereby improving the processing adaptability of the electrolyte powder. At the same time, the precise control of the product particle size to ≤75μm through a 200-mesh sieve enables dense compaction and uniform thickness of the subsequent electrolyte layer, facilitating continuous coating and assembly of all-solid-state battery electrodes, reducing electrode-electrolyte interface contact resistance and batch-to-batch performance differences, and ensuring the cycle stability and rate performance of the all-solid-state battery.

[0043] The protective gas includes any one or a combination of at least two of argon, helium, and neon, preferably argon.

[0044] The protective gas contains less than 1 ppm of water and less than 1 ppm of oxygen.

[0045] The ball milling process is preferably a high-energy mechanical ball milling process.

[0046] This application also proposes the use of oxysulfide solid electrolytes in solid-state batteries for new energy vehicles.

[0047] This application also proposes the application of the oxysulfide solid electrolyte prepared by the preparation method in an all-solid-state lithium-ion secondary battery.

[0048] For example, using a high-energy ball milling-solid-state sintering method, lithium sulfide (Li2S), lithium oxide (Li2O), tungsten disulfide (WS2), and lithium iodide (LiI) were weighed according to stoichiometric ratio in an argon glove box with strict water and oxygen control (H2O and O2 both <0.1ppm). Anhydrous n-hexane was used as the dispersion medium, and the mixture was ball-milled for 15 hours in a zirconia ball mill at a ball-to-material ratio of 20:1 and a rotation speed of 400 rpm to obtain amorphous precursor powder. Subsequently, the powder was pressed into a green body with a thickness of about 500 μm under a uniaxial pressure of 200 MPa, and sintered at 350 °C for 4 hours in a high-purity argon atmosphere at a temperature of 2 °C / min. After furnace cooling, a series of dense oxysulfide solid electrolytes with the general formula xLi2O·yLiWS2·Iz were obtained. Each electrolyte was assembled into a solid-state battery with a lithium nickel cobalt manganese oxide (NCM811) composite cathode and a lithium metal anode. Cyclic tests were conducted at a constant temperature of 25℃ and a charge / discharge rate of 1C / 1C, and the room temperature ionic conductivity was measured simultaneously. The specific results are shown in the table below:

[0049] Table 1. Summary of room temperature performance of solid electrolytes with different oxysulfide compositions

[0050] x=0, y=1, z=0 <![CDATA[LiWS2]]> 7mS / cm 700 times x=1, y=1, z=1 <![CDATA[Li3WOS2I]]> 6mS / cm 1000 times x=2, y=1, z=1 <![CDATA[Li5WO2S2I]]> 4mS / cm 1200 times x=3, y=1, z=1 <![CDATA[Li7WO3S2I]]> 2mS / cm 1400 times x=1, y=2, z=1 <![CDATA[Li4W2OS4I]]> 5mS / cm 1100 times x=2, y=2, z=1 <![CDATA[Li6W2O2S4I]]> 3mS / cm 1300 times x=3, y=2, z=1 <![CDATA[Li8W2O3S4I]]> 1mS / cm 1500 times

[0051] As clearly shown in the table, LiWS2 without oxygen and iodine doping achieved the highest ionic conductivity of 7 mS / cm due to its highly ordered sulfide sublattice, but the severe interfacial side reactions between it and the oxide cathode and lithium metal anode resulted in a cycle life of only 700 cycles. After introducing oxygen and iodine, the conductivity decreased systematically with increasing oxygen content, but the cycle performance improved dramatically. In the y=1 series, the cycle count of Li3WO3S2I, Li5WO2S2I, and Li7WO3S2I increased to 1000 cycles respectively. The cycle life of Li4W2O3S4I, Li6W2O2S4I, and Li8W2O3S4I reached 1100, 1300, and 1500 cycles, respectively, with the capacity retention rate always above 90% over the entire cycle. Among them, the optimal composition Li8W2O3S4I achieved a long cycle life of 1500 cycles with a practical conductivity of 1 mS / cm, which is more than twice as long as the undoped system. This breakthrough in conductivity and interface stability stems from the unique synergistic mechanism of oxygen / iodine dual doping: X-ray diffraction confirmed that oxygen ions partially replace sulfur sites, forming high-strength W–O and Li–O bonds, effectively stabilizing the local framework and suppressing sulfur volatilization and continuous side reactions with the electrodes during cycling; X-ray photoelectron spectroscopy analysis showed that iodine ions preferentially accumulate at grain boundaries and the anode interface, generating an extremely thin nanoscale LiI interface phase in situ, significantly reducing the interface charge transfer impedance, homogenizing lithium ion deposition, and effectively suppressing lithium dendrite growth; at the same time, increasing the y value improves the WS2 content, providing richer lithium ion conduction pathways and endowing the interface with more active passivation sites, further enhancing long-term cycling stability.

[0052] Example 2

[0053] This application provides an oxygen sulfide solid electrolyte, characterized in that the chemical composition of the oxygen sulfide solid electrolyte is xLi₂O·yLiWS₂·I. z , where 0≤x≤3, 0≤y≤2, 0≤z≤1.

[0054] The raw materials for the oxysulfide solid electrolyte are Li2O, LiWS2 and I.

[0055] In this context, Li2O in the raw material can be replaced with Li2CO3 or LiOH.

[0056] The ionic conductivity of the oxysulfide solid electrolyte at 25°C is 4 mS / cm.

[0057] This application also proposes a method for preparing an oxysulfide solid electrolyte, such as... Figure 1 As shown, it includes the following steps:

[0058] S1: Mix raw materials Li2O, LiWS2 and elemental I and ball mill them, controlling the ball milling speed at 350 rpm and the ball milling time at 8 h, to obtain a mixed powder with a particle size of 50 μm;

[0059] It is understood that in the embodiments of this application, the three raw materials, Li2O, LiWS2, and elemental I, are mechanically ball-milled at a controlled milling speed of 350 rpm and a milling time of 8 hours to ensure that a mixed powder with a uniform particle size distribution of 50 μm is obtained. This fully utilizes the mechanochemical effect to achieve molecular-level uniform mixing of the components at the nanoscale. For the subsequent heat treatment process, the activation energy of the reaction can be significantly reduced, allowing the crystal to complete ordered growth at low temperatures. The precisely controlled particle size range can avoid particle agglomeration and abnormal grain growth. This maximizes the reaction efficiency and product purity between raw materials and lays the microstructural foundation for the subsequent formation of continuous and uniform lithium-ion transport channels. It effectively avoids problems such as component segregation, excessive particle size differences, and insufficient reaction caused by traditional solid-phase mixing, ensuring the ionic conductivity and batch stability of the oxysulfide solid electrolyte.

[0060] S2: The mixed powder obtained in S1 is placed in a protective gas atmosphere for heat treatment. The protective gas flow rate is controlled at 100 sccm, the heat treatment temperature is 350℃, and the heat treatment time is 8h to obtain crude oxygen sulfide solid electrolyte.

[0061] It is understood that, in the embodiments of this application, by placing the product in a protective gas atmosphere with a water content of <1ppm and an oxygen content of <1ppm, and controlling the gas flow rate of 100sccm, the heat treatment temperature of 350℃, and the heat treatment time of 8h, the crude oxygen sulfide solid electrolyte with a complete crystal structure and free from oxidation and hydrolysis impurities is ensured. Regarding the crystal growth process, this promotes short-range atomic diffusion to form a continuous three-dimensional lithium-ion transport framework, while eliminating internal stress and lattice defects introduced by high-energy ball milling. Regarding product purity and stability, the flowing protective gas can promptly remove volatile impurities such as CO2 and H2O generated by thermal decomposition, completely isolating the sulfide framework from external moisture and oxygen. This maximizes the retention of highly active ion transport channels synergistically constructed by the ternary components, while avoiding abnormal grain growth and sulfide decomposition caused by high temperatures. It effectively avoids problems such as decreased ionic conductivity, impurity residue, and batch performance fluctuations caused by traditional high-temperature sintering, ensuring the high ionic conductivity and chemical stability of the oxygen sulfide solid electrolyte.

[0062] S3: The crude oxygen sulfide solid electrolyte obtained in S2 is ground under a protective gas. The ground powder is then sieved through a 200-mesh sieve, and materials with a mesh size ≥ 200 are collected to obtain the oxygen sulfide solid electrolyte.

[0063] It is understood that in this embodiment, the crude oxygen sulfide solid electrolyte obtained in S2 is ground under a protective gas with a water content of <1ppm and an oxygen content of <1ppm. The ground powder is then sieved through a 200-mesh sieve, and materials with a mesh size of ≥200 mesh are collected. This process not only isolates the electrolyte from moisture and oxygen in the air by creating an inert atmosphere that is completely anhydrous and oxygen-free, thus preventing hydrolysis and oxidation reactions that could generate toxic hydrogen sulfide gas and impurities during grinding, but also ensures that the chemical purity and core ion transport performance of the electrolyte do not degrade. Furthermore, mechanical grinding effectively breaks up the soft agglomerates formed during heat treatment, making the particles monodisperse and preventing uneven coating and interface defects caused by large particle agglomeration, thereby improving the processing adaptability of the electrolyte powder. At the same time, the precise control of the product particle size to ≤75μm through a 200-mesh sieve enables dense compaction and uniform thickness of the subsequent electrolyte layer, facilitating continuous coating and assembly of all-solid-state battery electrodes, reducing electrode-electrolyte interface contact resistance and batch-to-batch performance differences, and ensuring the cycle stability and rate performance of the all-solid-state battery.

[0064] The protective gas includes any one or a combination of at least two of argon, helium, and neon, preferably argon.

[0065] The protective gas contains less than 1 ppm of water and less than 1 ppm of oxygen.

[0066] The ball milling process is preferably a high-energy mechanical ball milling process.

[0067] This application also proposes the use of oxysulfide solid electrolytes in solid-state batteries for new energy vehicles.

[0068] This application also proposes the application of the oxysulfide solid electrolyte prepared by the preparation method in an all-solid-state lithium-ion secondary battery.

[0069] The preparation method of this embodiment is the same as that of Embodiment 1.

[0070] Example 3

[0071] This application provides an oxygen sulfide solid electrolyte, characterized in that the chemical composition of the oxygen sulfide solid electrolyte is xLi₂O·yLiWS₂·I. z , where 0≤x≤3, 0≤y≤2, 0≤z≤1.

[0072] The raw materials for the oxysulfide solid electrolyte are Li2O, LiWS2 and I.

[0073] In this context, Li2O in the raw material can be replaced with Li2CO3 or LiOH.

[0074] The ionic conductivity of the oxysulfide solid electrolyte at 25°C is 7 mS / cm.

[0075] This application also proposes a method for preparing an oxysulfide solid electrolyte, such as... Figure 1 As shown, it includes the following steps:

[0076] S1: Mix raw materials Li2O, LiWS2 and elemental I and ball mill them, controlling the ball milling speed at 500 rpm and the ball milling time at 12 h, to obtain a mixed powder with a particle size of 100 μm;

[0077] It is understood that in the embodiments of this application, the three raw materials, Li2O, LiWS2, and elemental I, are mechanically ball-milled at a controlled milling speed of 500 rpm for 12 hours to ensure that a mixed powder with a uniform particle size distribution of 100 μm is obtained. This fully utilizes the mechanochemical effect to achieve molecular-level uniform mixing of the components at the nanoscale. For the subsequent heat treatment process, the activation energy of the reaction can be significantly reduced, allowing the crystals to complete ordered growth at a low temperature of 200-500℃. The precisely controlled particle size range can avoid particle agglomeration and abnormal grain growth. This maximizes the reaction efficiency and product purity between the raw materials and lays the microstructural foundation for the subsequent formation of continuous and uniform lithium-ion transport channels. It effectively avoids problems such as component segregation, excessive particle size differences, and insufficient reaction caused by traditional solid-phase mixing, ensuring the ionic conductivity and batch stability of the oxysulfide solid electrolyte.

[0078] S2: The mixed powder obtained in S1 is placed in a protective gas atmosphere for heat treatment. The protective gas flow rate is controlled at 150 sccm, the heat treatment temperature is 500℃, and the heat treatment time is 12h to obtain crude oxygen sulfide solid electrolyte.

[0079] It is understood that, in the embodiments of this application, by placing the product in a protective gas atmosphere with a water content of <1ppm and an oxygen content of <1ppm, and controlling the gas flow rate of 150sccm, the heat treatment temperature of 500℃, and the heat treatment time of 12h, the crude oxygen sulfide solid electrolyte with a complete crystal structure and free from oxidation and hydrolysis impurities is ensured. Regarding the crystal growth process, this promotes short-range atomic diffusion to form a continuous three-dimensional lithium-ion transport framework, while eliminating internal stress and lattice defects introduced by high-energy ball milling. Regarding product purity and stability, the flowing protective gas can promptly remove volatile impurities such as CO2 and H2O generated by thermal decomposition, completely isolating the sulfide framework from external moisture and oxygen. This maximizes the retention of highly active ion transport channels synergistically constructed by the ternary components, while avoiding abnormal grain growth and sulfide decomposition caused by high temperatures. It effectively avoids problems such as decreased ionic conductivity, impurity residue, and batch performance fluctuations caused by traditional high-temperature sintering, ensuring the high ionic conductivity and chemical stability of the oxygen sulfide solid electrolyte.

[0080] S3: The crude oxygen sulfide solid electrolyte obtained in S2 is ground under a protective gas. The ground powder is then sieved through a 200-mesh sieve, and materials with a mesh size ≥ 200 are collected to obtain the oxygen sulfide solid electrolyte.

[0081] It is understood that in this embodiment, the crude oxygen sulfide solid electrolyte obtained in S2 is ground under a protective gas with a water content of <1ppm and an oxygen content of <1ppm. The ground powder is then sieved through a 200-mesh sieve, and materials with a mesh size of ≥200 mesh are collected. This process not only isolates the electrolyte from moisture and oxygen in the air by creating an inert atmosphere that is completely anhydrous and oxygen-free, thus preventing hydrolysis and oxidation reactions that could generate toxic hydrogen sulfide gas and impurities during grinding, but also ensures that the chemical purity and core ion transport performance of the electrolyte do not degrade. Furthermore, mechanical grinding effectively breaks up the soft agglomerates formed during heat treatment, making the particles monodisperse and preventing uneven coating and interface defects caused by large particle agglomeration, thereby improving the processing adaptability of the electrolyte powder. At the same time, the precise control of the product particle size to ≤75μm through a 200-mesh sieve enables dense compaction and uniform thickness of the subsequent electrolyte layer, facilitating continuous coating and assembly of all-solid-state battery electrodes, reducing electrode-electrolyte interface contact resistance and batch-to-batch performance differences, and ensuring the cycle stability and rate performance of the all-solid-state battery.

[0082] The protective gas includes any one or a combination of at least two of argon, helium, and neon, preferably argon.

[0083] The protective gas contains less than 1 ppm of water and less than 1 ppm of oxygen.

[0084] The ball milling process is preferably a high-energy mechanical ball milling process.

[0085] This application also proposes the use of oxysulfide solid electrolytes in solid-state batteries for new energy vehicles.

[0086] This application also proposes the application of the oxysulfide solid electrolyte prepared by the preparation method in an all-solid-state lithium-ion secondary battery.

[0087] The preparation method of this embodiment is the same as that of Embodiment 1.

[0088] Comparative Example 1

[0089] This comparative example provides a method for preparing an oxygen sulfide solid electrolyte, which mainly includes the following preparation steps:

[0090] S1: Weigh Li2O and LiWS2 raw materials according to the stoichiometric ratio, wherein the molar ratio of Li2O to LiWS2 is 1:1. Place the two raw materials in a ball mill jar for high-energy mechanical ball milling, control the ball milling speed to be 350 rpm and the ball milling time to be 6 h, and obtain a mixed powder with a particle size of 100 nm.

[0091] S2: The mixed powder obtained in S1 was placed in an argon atmosphere for heat treatment. The argon flow rate was controlled at 100 sccm, the argon water content was <1 ppm, the oxygen content was <1 ppm, the heat treatment temperature was 350℃, and the heat treatment time was 6h to obtain crude oxygen sulfide solid electrolyte.

[0092] S3: The crude oxygen sulfide solid electrolyte obtained in S2 is ground under argon protection. The ground powder is sieved through a 200-mesh sieve, and materials with a mesh size ≥ 200 are collected to obtain an oxygen sulfide solid electrolyte that does not contain iodine.

[0093] Comparative Example 2

[0094] This comparative example provides a method for preparing an oxygen sulfide solid electrolyte, which mainly includes the following preparation steps:

[0095] S1: Weigh LiWS2 and elemental I raw materials according to the stoichiometric ratio, wherein the molar ratio of LiWS2 to I is 1:1. Place the two raw materials in a ball mill jar for high-energy mechanical ball milling, control the ball milling speed at 350 rpm and the ball milling time at 6 h, and obtain a mixed powder with a particle size of 50 μm.

[0096] S2: The mixed powder obtained in S1 was placed in an argon atmosphere for heat treatment. The argon flow rate was controlled at 100 sccm, the argon water content was <1 ppm, the oxygen content was <1 ppm, the heat treatment temperature was 350℃, and the heat treatment time was 6h to obtain crude oxygen sulfide solid electrolyte.

[0097] S3: The crude oxygen sulfide solid electrolyte obtained in S2 is ground under argon protection. The ground powder is sieved through a 200-mesh sieve, and materials with a mesh size ≥ 200 mesh are collected to obtain an oxygen sulfide solid electrolyte that does not contain lithium oxide.

[0098] Comparative Example 3

[0099] This comparative example provides a method for preparing an oxygen sulfide solid electrolyte, which mainly includes the following preparation steps:

[0100] S1: Weigh Li2O and elemental I raw materials according to the stoichiometric ratio, wherein the molar ratio of Li2O to I is 1:1. Place the two raw materials in a ball mill jar for high-energy mechanical ball milling, control the ball milling speed at 350 rpm and the ball milling time at 6 h, and obtain a mixed powder with a particle size of 100 μm.

[0101] S2: The mixed powder obtained in S1 was placed in an argon atmosphere for heat treatment. The argon flow rate was controlled at 100 sccm, the argon water content was <1 ppm, the oxygen content was <1 ppm, the heat treatment temperature was 350℃, and the heat treatment time was 6h to obtain crude oxygen sulfide solid electrolyte.

[0102] S3: The crude oxygen sulfide solid electrolyte obtained in S2 is ground under argon protection. The ground powder is sieved through a 200-mesh sieve, and materials with a mesh size ≥ 200 mesh are collected to obtain an oxygen sulfide solid electrolyte that does not contain lithium tungsten disulfide.

[0103] Performance testing

[0104] The hydrolysis resistance of the oxygen sulfide solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3 was analyzed using an air stability test method. Each sample was exposed to air at 25°C and 50% relative humidity for 24 hours. The ionic conductivity before and after exposure was then measured, and the conductivity retention rate (conductivity after exposure / initial conductivity × 100%) was calculated. The release of hydrogen sulfide gas was also simultaneously monitored. Performance test data are shown in Table 2.

[0105] Table 2 Air stability test

[0106] Example 1 1.00 0.942 94.2 <0.1 Example 2 4.00 3.68 92.0 <0.1 Example 3 7.00 6.13 87.6 <0.1 Comparative Example 1 0.81 0.15 18.5 8.5 Comparative Example 2 0.65 0.10 15.4 2.3 Comparative Example 3 0.32 0.04 12.5 0.5

[0107] As shown in Table 2, the oxysulfide solid electrolytes prepared in Examples 1-3 of this invention all exhibited excellent air stability after being exposed to air at 25°C and 50% relative humidity for 24 hours. The conductivity retention rates were generally in the high range of 87.6%-94.2%, and the simultaneously detected H2S release was all below 0.1 ppm. Specifically, Example 1 had an initial conductivity of 1.00 mS / cm, which remained at 0.942 mS / cm after exposure, achieving a retention rate of 94.2%; Example 2 had an initial conductivity of 4.00 mS / cm, which remained at 3.68 mS / cm after exposure, achieving a retention rate of 92.0%; and Example 3, despite having the highest initial conductivity of 7.00 mS / cm, still maintained a conductivity of 6.13 mS / cm after exposure, achieving a retention rate of 87.6%. The co-doping strategy utilizes oxygen atoms, which have higher electronegativity, to partially replace sulfur atoms in the sulfide framework, forming Li-O and WO bonds with higher bond energies. This fundamentally reduces the electron cloud density and reactivity of the remaining sulfur atoms, blocking the nucleophilic substitution reaction pathway of water molecules. This mechanism avoids the generation of toxic H2S gas and prevents crystal framework breakage and lithium-ion transport channel collapse. The synergistic effect of these three factors maintains high ionic conductivity while improving chemical stability.

[0108] In contrast, the conductivity retention rates of Comparative Examples 1-3 showed a precipitous drop, and the H2S release increased significantly, revealing different failure modes due to the absence of key components. Comparative Example 1 (lacking component I) exhibited a conductivity of only 0.15 mS / cm after exposure, with a retention rate plummeting to 18.5%, and released as much as 8.5 ppm of H2S gas. This indicates that the lack of iodine doping prevents the formation of a stable oxysulfide solid solution, and the highly reactive sulfur atoms in the framework are completely exposed to hydrolytic corrosion; Comparative Example 2 (lacking component I)... The conductivity of the component after exposure was 0.10 mS / cm, the retention rate was 15.4%, and the H2S release was 2.3 ppm, indicating that the absence of oxygen atoms had a stabilizing effect on the framework, and the sulfide framework rapidly hydrolyzed and failed in humid air; Comparative Example 3 (without oxygen atoms) The component lacks a core sulfide structure, resulting in extremely low initial conductivity of only 0.32 mS / cm, which further decreases to 0.04 mS / cm after exposure, with a retention rate of only 12.5%, almost completely losing its ion transport capability. This further highlights the limitations of the embodiments described in this application. The decisive role of ternary components in constructing highly active and stable oxysulfide solid electrolytes.

[0109] The ionic conductivity and electrochemical stability window of the oxysulfide solid electrolytes prepared in Examples 1-3 and Comparative Examples 1-3 were analyzed using AC impedance spectroscopy (blocked electrode, frequency range 1Hz-7MHz, perturbation voltage 10mV) and linear sweep voltammetry (scan rate 0.1mV / s). The powder samples were cold-pressed into dense ceramic sheets under 300MPa pressure, and their lithium-ion conductivity and oxidation decomposition potential (vs. Li / Li⁺) at 25℃ were tested. The performance test data are shown in Table 3.

[0110] Table 3 Ionic conductivity and electrochemical window test results

[0111] Example 1 1.00 4.6 4.7 Example 2 4.00 4.8 4.9 Example 3 7.00 5.0 5.1 Comparative Example 1 0.81 3.8 3.9 Comparative Example 2 0.65 3.5 3.6 Comparative Example 3 0.32 3.1 3.2

[0112] As shown in Table 3, the oxysulfide solid electrolytes prepared in Examples 1-3 of this invention exhibit the dual advantages of high ionic conductivity and a wide electrochemical window at 25°C. The ionic conductivity significantly increased from 1.00 mS / cm to 7.00 mS / cm with composition optimization, far exceeding that of traditional binary systems; simultaneously, its electrochemical stability window broadened to an ultra-wide range of 4.6-5.0 V (vs. Li / Li⁺). The oxidation decomposition potential in Example 3 reached as high as 5.1 V. The introduction of more electronegative oxygen atoms increased the oxidation potential at the valence band top, fundamentally suppressing the oxidation decomposition of the electrolyte at high voltages; while the doping of iodine atoms effectively reduced the reduction potential at the conduction band bottom, enhancing interfacial compatibility with the lithium metal anode. The synergistic effect of these two factors fundamentally breaks the bottleneck of mutual constraint between ionic conductivity and electrochemical stability when using single-element doping, enabling the electrolyte to stably match high-voltage cathode materials such as lithium nickel manganese oxide and lithium-rich manganese-based materials, laying a core material foundation for achieving high energy density in all-solid-state batteries.

[0113] In contrast, the ionic conductivity and electrochemical window of Comparative Examples 1-3 were significantly suppressed after the absence of any component in the ternary structure, and the degradation trend was closely related to the function of the missing component. Comparative Example 1 (missing component I) had an ionic conductivity of only 0.81 mS / cm, an electrochemical window narrowed to 3.8 V, and an oxidation decomposition potential of only 3.9 V, proving that the lack of iodine doping could not optimize the reduction potential, resulting in poor interfacial compatibility and insufficient continuity of lithium-ion transport channels. Comparative Example 2 (missing component Li2O) had a conductivity of 0.65 mS / cm and an electrochemical window of 3.5 V, indicating that the lack of oxygen atoms had a stabilizing effect on the framework and an increase in oxidation potential, and the electrolyte began to decompose at low voltage. Comparative Example 3 (missing component LiWS2) completely lost the core sulfide lithium-ion conduction framework, with an ionic conductivity of only 0.32 mS / cm and an oxidation decomposition potential of only 3.2 V, making it almost useless for practical applications. These comparative results clearly reveal that only the uniform composite of the xLi2O・yLiWS2・Iz ternary components at the molecular scale in the embodiments of this application can simultaneously achieve excellent comprehensive performance of high ionic conductivity and ultra-wide electrochemical window through the O / I co-doping synergistic mechanism.

[0114] The particle size control accuracy and batch stability of the preparation processes in Examples 1-3 and Comparative Examples 1-3 were analyzed using a laser particle size analyzer and batch repeatability verification method. Three batches of each example and comparative example were prepared using the same process. The D50 particle size of the electrolyte powder that ultimately passed through a 200-mesh sieve in each batch was tested, as well as the fluctuation range of ionic conductivity between batches. The coefficient of variation (CV value, i.e., standard deviation / mean value × 100%) was calculated. The performance test data are shown in Table 4.

[0115] Table 4. Particle size control and batch stability test

[0116] Example 1 28.5±0.8 0.98-1.02 1.7 Example 2 34.2±0.9 3.94-4.05 1.2 Example 3 40.1±1.1 6.90-7.10 1.1 Comparative Example 1 48.7±5.8 0.62-0.98 18.5 Comparative Example 2 52.3±6.2 0.45-0.81 23.2 Comparative Example 3 55.1±7.1 0.18-0.43 31.5

[0117] As shown in Table 4, the preparation processes of Examples 1-3 of this invention demonstrate excellent particle size control precision and batch-to-batch performance stability. After sieving through a 200-mesh sieve, the final product D50 particle size fluctuation is extremely small, with a standard deviation of only 0.8-1.1 μm, and the coefficient of variation (CV) of the ionic conductivity of the three batches is as low as 1.1%-1.7%. In Example 3, under the process conditions of a maximum heat treatment temperature of 500℃ and a maximum heat treatment time of 12 hours, the batch conductivity remained stable at 6.90-7.10 mS / cm, with a CV value of only 1.1%. Low-temperature heat treatment at 200-500℃ under a flowing protective gas with water and oxygen content both <1 ppm, and the molecular-level uniform mixing achieved by high-energy ball milling ensured the homogeneous mixing of xLi₂O·yLiWS₂·I z During the heat treatment process, the ternary components form a uniform phase and grow crystals in an orderly manner. The flowing protective gas also removes any volatile impurities that may remain, ensuring the purity and uniformity of the product. The anhydrous and oxygen-free grinding and sieving process effectively ensures the monodisperse state of the final particles, eliminating product unevenness caused by particle agglomeration and ensuring a high degree of consistency in the performance of different batches of products from the source.

[0118] In contrast, the final D50 particle size of Comparative Examples 1-3 showed huge fluctuations, with standard deviations ranging from 5.8 to 7.1 μm, and the batch-to-batch conductivity variation coefficient (CV) soared to 18.5%-31.5%. Comparative Example 1, lacking iodine, could not form a complete crystal lattice framework even with the same ball milling and heat treatment processes, resulting in uneven distribution of impurity phases and severe particle size dispersion. Comparative Example 2, lacking lithium oxide, could not construct a stable oxygen bridging network using only LiWS2 and I, leading to abnormally large and uneven particle growth during heat treatment. Comparative Example 3, lacking lithium tungsten disulfide, was essentially... The mixture with I cannot form a continuous lithium-ion conductive phase, exhibiting extremely low conductivity and significant batch-to-batch variations. These comparative results profoundly reveal that the absence of any link in a ternary system leads to uncontrollable and substantial fluctuations in phase composition and microstructure due to the inability to form a stable ternary solid solution structure. This further highlights the advantages of xLi₂O·yLiWS₂·I in the embodiments of this application. z The design of ternary components and their matching precision preparation process are of decisive value for achieving the large-scale production of oxysulfide solid electrolytes with high ionic conductivity and high batch stability.

[0119] In summary, this application's embodiments utilize the inherent chemical bond regulation mechanism of oxygen and iodine co-doping, the molecular-level uniform mixing process achieved through high-energy ball milling, and the anhydrous and oxygen-free grinding and sieving control effect, combined with the synergistic effect of the xLi₂O・yLiWS₂・Iz ternary components, to prepare a high-performance oxygen sulfide solid electrolyte: oxygen atoms partially replace sulfur atoms in the sulfide framework to form high-bond-energy Li-O and WO bonds, blocking the nucleophilic substitution reaction pathway of water molecules, and are further enhanced by exposure to air at 25°C and 50% relative humidity for 24 hours. The test conditions resulted in an electrolyte conductivity retention rate of 87.6%-94.2% and H2S release of less than 0.1 ppm, significantly better than the comparative example (conductivity retention rate 12.5%-18.5%, H2S release 0.5-8.5 ppm). The oxygen atom-enhanced oxidation potential suppresses high-voltage oxidation decomposition, while the iodine atom-enhanced reduction potential enhances the interfacial compatibility of the lithium metal anode. Combined with the continuous lithium-ion transport channels constructed by the ternary solid solution, the electrolyte achieved an ionic conductivity of 1.00-7.00 at 25℃. The electrolyte exhibits significantly improved electrochemical stability (4.6-5.0 V) and electrochemical stability (4.7-5.1 V oxidation decomposition potential), compared to the comparative example (0.32-0.81 mS / cm ionic conductivity, 3.1-3.8 V electrochemical stability, 3.2-3.9 V oxidation decomposition potential). Low-temperature heat treatment with a flowing protective gas at 200-500℃ effectively removes volatile impurities, and the anhydrous and oxygen-free operation throughout the process effectively eliminates particle agglomeration. Combined with molecular-level uniform mixing ensuring homogeneous phase formation and orderly crystal growth, this results in a more efficient electrolyte. The final product has a D50 particle size standard deviation of only 0.8-1.1μm and a coefficient of variation of ionic conductivity of only 1.1%-1.7% across three batches, while the comparative sample shows deterioration (D50 particle size standard deviation of 5.8-7.1μm and coefficient of variation of 18.5%-31.5%). The synergistic effect of high air stability, ultra-wide electrochemical window and excellent batch stability enables the electrolyte to be stably matched with high-voltage cathode materials such as lithium nickel manganese oxide and lithium-rich manganese-based materials, thereby improving the application performance of oxysulfide solid electrolytes in high-energy-density all-solid-state batteries.

[0120] According to the embodiments of this application, an oxysulfide solid electrolyte and its preparation method are proposed. A ternary component design of xLi₂O・yLiWS₂・Iz and a high-energy mechanical ball milling-low-temperature heat treatment composite preparation process are used. By introducing more electronegative oxygen atoms from Li₂O, sulfur atoms in the sulfide framework are partially replaced, forming Li-O and WO bonds with significantly higher bond energies. This reduces the electron cloud density and reactivity of the remaining sulfur atoms, fundamentally blocking the nucleophilic substitution reaction pathway of water molecules. This avoids the generation of toxic hydrogen sulfide gas and prevents crystal framework breakage and lithium ion exchange. The collapse of the transport channel allows the electrolyte to retain 87.6%-94.2% conductivity and release less than 0.1 ppm of hydrogen sulfide after 24 hours of exposure to air at 25°C and 50% relative humidity. Simultaneously, the ionic conductivity is significantly improved to 1-7 mS / cm, far superior to traditional binary oxygen sulfide electrolytes. The raw material Li₂O can be replaced with industrially common and inexpensive Li₂CO₃ or LiOH, both of which can be completely thermally decomposed within a heat treatment temperature range of 200-500°C, generating highly active nano-sized lithium oxide in situ, which then reacts fully with other raw materials to form… The uniform oxysulfide crystal structure allows carbon dioxide and water vapor produced during decomposition to be promptly carried out of the system by a continuous flow of protective gas at 50-150 sccm, leaving no solid impurities and preventing side reactions, thus ensuring electrolyte purity and performance stability. By controlling the water content and oxygen content of the protective gas to <1 ppm and the flow rate to 50-150 sccm, oxidation and corrosion from moisture and oxygen in the air are effectively prevented. Combined with a ball milling speed of 200-500 rpm and a ball milling time of 2-12 hours, the particle size of the mixed powder is precisely controlled within 100 nm-100 nm. The particles, measured in μm, are ultimately sieved through a 200-mesh sieve to obtain a product with uniform particle size, ensuring consistent performance across different batches. The electrolyte's electronic structure is synergistically optimized through co-doping of oxygen and iodine atoms. Oxygen atoms increase the valence band top oxidation potential, suppressing oxidation decomposition under high voltage, while iodine atoms lower the conduction band bottom reduction potential, enhancing interfacial compatibility with the lithium metal anode. This synergistic effect avoids the mutual constraints on ionic conductivity and stability caused by single-element doping, broadening the electrochemical window to 4.6-5.0 V vs Li / Li⁺, enabling stable matching with high-voltage cathode materials such as lithium nickel manganese oxide and lithium-rich manganese-based materials. This system overcomes the technical bottlenecks of traditional oxysulfide solid electrolytes, including poor air stability, high preparation costs, poor batch consistency, mutual constraints between ionic conductivity and electrochemical stability, and inability to match high-voltage cathodes, thus improving the overall performance and large-scale application potential of the electrolyte.

[0121] Although embodiments of this application have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the appended claims and their equivalents.

[0122] The present application and its embodiments have been described above. This description is not restrictive, and the actual application is not limited thereto. In conclusion, if a person skilled in the art is inspired by this description and designs a similar structure and embodiment without departing from the spirit of this application, such design should fall within the protection scope of this application.

Claims

1. A sulfide solid electrolyte, characterized in that, The chemical composition of the oxysulfide solid electrolyte is xLi₂O·yLiWS₂·I. z , where 0≤x≤3, 0≤y≤2, 0≤z≤1.

2. The oxysulfide solid electrolyte according to claim 1, characterized in that, The raw material sources for the oxysulfide solid electrolyte are Li2O, LiWS2 and I.

3. The oxysulfide solid electrolyte according to claim 2, characterized in that, The Li2O in the raw material can be replaced with Li2CO3 or LiOH.

4. The oxysulfide solid electrolyte according to claim 1, characterized in that, The ionic conductivity of the oxysulfide solid electrolyte at 25°C is 1-7 mS / cm.

5. A method for preparing an oxysulfide solid electrolyte as described in any one of claims 1-4, characterized in that, Includes the following steps: S1: Mix raw materials Li2O, LiWS2 and elemental I and ball mill them, controlling the ball milling speed to 200-500 rpm and the ball milling time to 2-12 h, to obtain a mixed powder with a particle size of 100nm-100μm; S2: The mixed powder obtained in S1 is placed in a protective gas atmosphere for heat treatment, and the protective gas flow rate is controlled at 50-150 sccm, the heat treatment temperature is 200-500℃, and the heat treatment time is 2-12h to obtain crude oxygen sulfide solid electrolyte. S3: The crude oxygen sulfide solid electrolyte obtained in S2 is ground under a protective gas. The ground powder is then sieved through a 200-mesh sieve, and materials with a mesh size ≥ 200 are collected to obtain the oxygen sulfide solid electrolyte.

6. The method for preparing an oxysulfide solid electrolyte according to claim 5, characterized in that, The protective gas includes any one or a combination of at least two of argon, helium, and neon, preferably argon.

7. The method for preparing an oxysulfide solid electrolyte according to claim 5, characterized in that, The protective gas has a water content of <1 ppm and an oxygen content of <1 ppm.

8. The method for preparing an oxysulfide solid electrolyte according to claim 5, characterized in that, The ball mill is preferably a high-energy mechanical ball mill.

9. A oxysulfide solid electrolyte according to any one of claims 1-4, characterized in that, The oxysulfide solid electrolyte is used in solid-state batteries for new energy vehicles.

10. The application of an oxysulfide solid electrolyte prepared by the preparation method according to any one of claims 1-4, and the oxysulfide solid electrolyte according to claim 9, in an all-solid-state lithium-ion secondary battery.